The prevalence of risk for hearing impairment in newborns with congenital syphilis in a newborn hearing screening program (NHS) - Oliveira, Thalita da Silva; Dutra, Monique Ramos Paschoal; Nunes-Araujo, Aryelly Dayane da Silva; Silva, Aline Roberta Xavier da; Oliveira, Gabriel Barros Lins Lelis de; Silva, Gleyson José Pinheiro Caldeira; Valentim, Ricardo Alexsander de Medeiros; Balen, Sheila Andreoli (Frontiers in Public Health, 2023)
Objective: Study the prevalence of risk for hearing impairment in neonates with congenital syphilis in a Newborn Hearing Screening Program. Study design:Retrospective, documentary, cross-sectional study. The sample consisted of newborns, born from January 2019 to December 2021, who underwent neonatal hearing screening in a public maternity hospital. Demographic data, presence and specification of risk indicators for hearing impairment (RIHL) were collected. In retest cases, the results and the final conduct were also collected. For data analysis, the Kruskal-Wallis and Posthoc Conover-Iman tests were used, comparing the groups that passed and failed the hearing screening that had RIHL, using a significance level of p<0.5. Results: Among the RIHL observed in the sample, prematurity was more frequent both in newborns who passed the screening (55.26%) and those who failed the test (45.67%). Congenital syphilis was the ninth most frequent RIHL (8.04%) among newborns who passed the test and the fifteenth factor (3.03%) with the highest occurrence in those who failed the hearing screening. When comparing the two groups (Pass and Fail) significant differences (p < 0.05) were found between them.Congenital syphilis was the ninth risk indicator for the most common hearing impairment and, in isolation, did not present a risk for failure in neonatal hearing screening. It is noteworthy that congenital syphilis can cause late hearing loss during child development, thus, there is an indication of audiological monitoring of these neonates.